2021
DOI: 10.3390/su13179912
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries in the Context of Attaining Sustainable Development Goals (SDGs) in Bangladesh: COVID-19 Impacts and Future Prospects

Abstract: Fisheries and the aquaculture sector can play a significant role in the achievement of several of the goals of the 2030 Sustainable Development agenda. However, the current COVID-19 situation can negatively impact the fisheries sector, impeding the pace of the achievement of development goals. Therefore, this paper highlighted the performance and challenges of the fisheries sector in Bangladesh, emphasising the impact of COVID-19 and the significance of this sector for achieving the Sustainable Development Goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 34 publications
0
25
0
1
Order By: Relevance
“…For example, between 1980 and 2008, per capita wheat consumption increased by 44% in Africa due to its convenience and ease of preparation [39]. Annually, almost 9 billion kg of bread items are manufactured [40], with an expected annual per capita intake of 41 to 303 kg [41]. Moreover, Asians are increasing their bread consumption.…”
Section: Economic Importance Of Bakery Productmentioning
confidence: 99%
“…For example, between 1980 and 2008, per capita wheat consumption increased by 44% in Africa due to its convenience and ease of preparation [39]. Annually, almost 9 billion kg of bread items are manufactured [40], with an expected annual per capita intake of 41 to 303 kg [41]. Moreover, Asians are increasing their bread consumption.…”
Section: Economic Importance Of Bakery Productmentioning
confidence: 99%
“…There were also reports that a total of 14 goals is severely hampered by COVID-19 with slightly positive outcomes in Bangladesh. Sunny et al (2021) explained that the fast-growing fisheries industry in Bangladesh is highly impacted by the pandemic. The closure of infrastructure services, labor calamity, high inflation, sudden health issues and decreased income as a result of the COVID-19 pandemic challenged the progress of SDGs in Bangladesh (Sunny et al 2021).…”
Section: Analysis Of Key Public Finance Sources For Bangladesh and Sr...mentioning
confidence: 99%
“…Sunny et al (2021) explained that the fast-growing fisheries industry in Bangladesh is highly impacted by the pandemic. The closure of infrastructure services, labor calamity, high inflation, sudden health issues and decreased income as a result of the COVID-19 pandemic challenged the progress of SDGs in Bangladesh (Sunny et al 2021). They pointed out that the SDGs like SDG 1: eliminate poverty, SDG 2: erase hungry, SDG 3: good health and well-being and SDG 12: responsible consumption and productions will be challenging to attain due to the significant reduction in people's income, nutrition, and food security.…”
Section: Analysis Of Key Public Finance Sources For Bangladesh and Sr...mentioning
confidence: 99%
“…Children living in poor sanitary conditions are more exposed to large amounts of pathogens, especially between 6 months and 2 years when they begin to crawl on the floor and throw objects into their mouths. Researchers further suggested that environmental entropy could be a significant factor in poor growth and could compromise the effectiveness of nutritional interventions ( 13 , 14 ). The relationship between diarrhea and malnutrition is complex, although it is well-known that malnourished children suffer frequent episodes of diarrhea, while a child's nutritional status is also affected after the diarrhea episode.…”
Section: Introductionmentioning
confidence: 99%